2019
DOI: 10.1093/mnras/stz1724
|View full text |Cite
|
Sign up to set email alerts
|

shiva: a dust destruction model

Abstract: We present a numerical tool Shiva designed to simulate the dust destruction in warm neutral, warm ionized, and hot ionized media under the influence of photo-processing, sputtering, and shattering. The tool is designed primarily to study the evolution of hydrogenated amorphous carbons (HACs), but options to simulate polycyclic aromatic hydrocarbons (PAHs), silicate and graphite grains are also implemented. HAC grain photo-processing includes both dehydrogenation and carbon atom loss. Dehydrogenation leads to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 74 publications
(102 reference statements)
0
35
0
2
Order By: Relevance
“…We also consider aromatization by SNe. According to Murga et al (2019), carbonaceous grains with a 0.1 µm are fully aromatized in a single SN shock. Therefore, we sim-ply adopt the following form for the aromatization efficiency in a single SN (ǫ ar,SN ):…”
Section: Separation Into Various Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider aromatization by SNe. According to Murga et al (2019), carbonaceous grains with a 0.1 µm are fully aromatized in a single SN shock. Therefore, we sim-ply adopt the following form for the aromatization efficiency in a single SN (ǫ ar,SN ):…”
Section: Separation Into Various Speciesmentioning
confidence: 99%
“…Nevertheless, it is interesting to investigate what kind of extinction curve our model produces if we adopt the carbonaceous dust properties similar to those adopted by Jones et al (2013). For this purpose, we adopt the optical properties of HAC adopted by Murga et al (2019): fully aliphatic grains with E g = 2.67 eV and fully aromatic grains with E g = 0.01 eV for the aromatic and non-aromatic components, respectively. We adopt the neutral case, but we confirmed that adopting the ionized HAC does not change the extinction curves.…”
Section: Other Possible Optical Properties Of Aromatic Carbonsmentioning
confidence: 99%
“…The model can be supplemented with the comprehensive simulations of the destruction processes of dust grains. This process was approximately considered in [40]; however, to date, we have developed a much more thorough model (called SHIVA) for the evolution of dust particles of different sizes [74]. This model will make it possible to understand whether there is a link between the swept dust grains and the appearance of extraplanar PAH particles in our and other galaxies.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…В модели динамика пыли определяется тремя силами: силой давления излучения, силой гравитационного притяжения и силой сопротивления межзвездного газа. В модель также включены процессы разрушения пыли, описанные в работах [7][8][9]. Ранее нами был детально исследован процесс выметания пылинок из нашей Галактики (Сивкова и др.…”
unclassified
“…Концентрация мелких пылинок не меняется в процессе столкновений с крупными частицами, поскольку считается, что при единичном столкновении мелкая пылинка уничтожается полностью, но фрагмент, отколовшийся от крупной пылинки, по размерам соответствует мелкой пыли. Кроме того, при столкновении двух крупных пылинок их размеры принимаются одинаковыми, поскольку в рамках моделей [8,9] считается, что при столкновении двух пылинок разных размеров меньшая частица всегда разрушается полностью. В дальнейшем планируется переход от рассмотрения динамики одной пылинки к рассмотрению движения ансамбля пылевых частиц, а также к более точному определению распределения их концентраций.…”
unclassified